Uji Kualitas Beberapa Pupuk Kompos yang Beredar di Kota Denpasar - TANTYA TANTRI P. T. N; A.A. NYOMAN SUPADMA; I DEWA MADE ARTHAGAMA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2016)
ABSTRACT Quality Test of Some Compost Fertilizer that circulate in Denpasar City This research to aims knowing the quality physical and chemical properties of 10 compost that meets several criteria according to SNI 19-7003-2004. This research starts from the sampling of fertilizers that have been circulate in the market. This research consists of several stages of laboratory analysis with that assessment parameter analysis results include water content, pH, N-total (method Kjeldhal), P2O5 and K2O total (extract method HCL 25%), C-organic (Walkley and Black method), and C/N ratio. Based on the results of physical and chemical quality test of the parameters which is conducted compost fertilizer, there are only 2 organic fertilizer most suitable from 10 types of fertilizers, namely fertilizer Bio-extrrim Trubus and Putri Liman Simantri 096 Blahbatuh, Gianyar has met the several criteria of compost according to SNI 19-7030-2004. The next compost fertilizer that does not comply with some of the SNI, namely Petrokimia Gresik, Good Compost Trubus, Bioorganic Simantri 027 Kelating, Kerambitan, Tabanan, Sapi Trubus, Bintang Tani Marga, Tabanan, Kambing Trubus, Higher For Grow and Agung Singapadu Gianyar, each fertilizer on average had higher levels of C-organic, C/N ratio, organic matter, which is not comply to the SNI 19-7030-2004. Keywords: quality test, physical and chemical properties, compost standard ISO (2004)